Integrating Inquiry-Based Learning into Guidance and Counseling Instruction: An Innovative Pedagogical Approach in Teacher Education - Heri Saptadi Ismanto; Muhammad Arief Budiman (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The growing emphasis on competency-based and reflective learning models in global counselor education, as promoted by UNESCO and OECD frameworks, highlights the need for pedagogical innovations that foster critical thinking and learner autonomy. Responding to this global demand, this study examines the implementation of the Inquiry-Based Learning (IBL) model in the Guidance and Counseling course and analyzes students’ responses to its application. Using a qualitative descriptive design and questionnaires, the research involved 68 undergraduate students in their second and fourth semesters. The findings indicate that IBL significantly enhanced students’ engagement (by 87%), critical thinking (by 76%), and conceptual understanding of counseling theories (by 81%). Students reported that IBL encouraged greater independence, reflection, and collaborative inquiry throughout the learning process. This study addresses a notable gap in the literature: empirical evidence on IBL in counselor education—particularly in non-Western contexts remains limited. Conceptually, the results affirm the alignment of IBL with constructivist and experiential learning paradigms, offering a model that bridges theory and practice in developing the foundational competencies of future counselors. In practice, these findings underscore the potential of IBL as a transformative strategy for cultivating globally relevant, contextually grounded counselor education. Keywords: inquiry-based learning, guidance and counseling, active learning, qualitative descriptive, counseling students